2019
DOI: 10.1186/s12984-019-0604-y
|View full text |Cite
|
Sign up to set email alerts
|

Offline effects of transcranial direct current stimulation on reaction times of lower extremity movements in people after stroke: a pilot cross-over study

Abstract: BackgroundTranscranial direct current stimulation (tDCS) is a non-invasive brain stimulation technique that has shown promise for rehabilitation after stroke. Ipsilesional anodal tDCS (a-tDCS) over the motor cortex increases corticospinal excitability, while contralesional cathodal tDCS (c-tDCS) restores interhemispheric balance, both resulting in offline improved reaction times of delayed voluntary upper-extremity movements. We aimed to investigate whether tDCS would also have a beneficial effect on delayed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
0
10
1
2
Order By: Relevance
“…Others have reported that tDCS may have a facilitating effect on reaction time with anodal stimulation over primary motor cortex, but Molero-Chamizo et al found that the effect was time dependent (Molero-Chamizo et al, 2018). Others have also failed to find an effect of tDCS (Coppens, Staring, Nonnekes, Geurts, & Weerdesteyn, 2019;Seidel & Ragert, 2019) We found more substantial improvements in measures of psychomotor speed, including a significant interaction of group by time for the WAIS-IV Coding subtest.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Others have reported that tDCS may have a facilitating effect on reaction time with anodal stimulation over primary motor cortex, but Molero-Chamizo et al found that the effect was time dependent (Molero-Chamizo et al, 2018). Others have also failed to find an effect of tDCS (Coppens, Staring, Nonnekes, Geurts, & Weerdesteyn, 2019;Seidel & Ragert, 2019) We found more substantial improvements in measures of psychomotor speed, including a significant interaction of group by time for the WAIS-IV Coding subtest.…”
Section: Discussioncontrasting
confidence: 42%
“…Others have reported that tDCS may have a facilitating effect on reaction time with anodal stimulation over primary motor cortex, but Molero-Chamizo et al found that the effect was time dependent (Molero-Chamizo et al, 2018). Others have also failed to find an effect of tDCS (Coppens, Staring, Nonnekes, Geurts, & Weerdesteyn, 2019;Seidel & Ragert, 2019) on reaction time. Our hypothesis of an effect on reaction time was based primarily on the nature of the training task (a fast-paced computer game), but neither statistical tests nor inspection of mean plots by groups (not presented) suggested an effect for either of the active treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary Tables 1 and 2 showed study characteristics of included studies. Finally, the present study included 16 and 12 articles for tDCS 5,7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23] and rTMS 6,8,[24][25][26][27][28][29][30][31][32][33] , respectively. Studies for tDCS included 10 RCTs (including 110 patients after stroke given tDCS and 110 patients given sham tDCS over motor cortex) and 6 crossover trails (including 102 patients after stroke).…”
Section: Search Resultsmentioning
confidence: 99%
“…Others have reported that tDCS may have a facilitating effect on reaction time with anodal stimulation over primary motor cortex, but Molero-Chamizo et al (2018) found that the effect was time dependent. Others have also failed to find an effect of tDCS ( Coppens et al, 2019 ; Seidel and Ragert, 2019 ) on reaction time. Our hypothesis of an effect on reaction time was based primarily on the nature of the training task (a fast-paced computer game), but neither statistical tests nor inspection of mean plots by groups (not presented) suggested an effect for either of the active treatment groups.…”
Section: Discussionmentioning
confidence: 99%